A MULTIDISCIPLINARY APPROACH TO LONG COVID ASSOCIATED WITH MYOFASCIAL PAIN SYNDROME: A CASE REPORT - A.S. YASINSKAYA; YU.O. NOVIKOV; M.B. TSYKUNOV; D.A. KIM; A.SH. KHUZHAKHMETOVA (Паёми Сино)
The development of long-term symptoms from coronavirus disease 2019 (COVID-19) can lead to persistent neurological disorders. In nearly one-third of patients, these symptoms manifest as back pain syndrome and dysfunction of the autonomic nervous system. The occurrence of back pain and the formation of trigger points in patients who have experienced coronavirus pneumonia are likely due to shared pathogenic mechanisms. These mechanisms may include damage to the musculoskeletal system, the development of fibrotic changes, and disruption of the neurotransmitter system. Case report: a 34-year-old male patient who contracted a new coronavirus infection caused by SARS-CoV-2, resulting in community-acquired polysegmental pneumonia involving 30% of the lung. After 2.5 months, he sought medical help from a neurologist due to complaints of persistent severe back pain, rapid fatigue, an unproductive cough, and malaise following physical exertion. A neurological examination, thermographic imaging, and variouslaboratory and imaging studies were conducted. The diagnosis was post-COVID-19 condition (long COVID), associated with myofascial pain syndrome of the latissimus dorsi, occurring in the setting of degenerative-dystrophic changes in the thoracic spine. This condition included severe pain and myotonic syndrome during the exacerbation period. Additionally, the patient was diagnosed with a disorder of the autonomic nervous system at the suprasegmental level, accompanied by an asthenic syndrome in the decompensation phase.